Framework for the quantitative assessment of the risk of leakage from LNG-fueled vessels by an event tree-CFD. (September 2016) - Fu, Shanshan; Yan, Xinping; Zhang, Di; Li, Chaoyu; Zio, Enrico
Abstract: Liquefied natural gas (LNG) is used as fuel in various kinds of vessels, e.g., passenger ship, ferry, cargo vessel and platform supply vessel (PSV). It is an eco-friendly bunker fuel with many advantages, like decreasing the emissions of SOX and particulate materials (PM) and meeting the international maritime organization (IMO) MARPOL Annex VI requirements on NOX emissions, and economic benefits compared to heavy fuel oil (HFO). However, the leakage of LNG-fuel is a threat for the safety of LNG-fueled vessels, due to its inflammable and explosive characteristics. This paper illustrates a framework for the quantitative risk assessment of LNG-fueled vessels with respect to potential leakage. For illustration purposes, reference is made to a typical LNG-fueled ship, as a representative case. Event tree analysis (ETA) and computational fluid dynamics (CFD) simulation are integrated for the investigation of the hazard, the analysis of the consequences, and the quantification the risk of the LNG leakage. The results of the study are used to provide risk control options (RCOs), in terms of optimal risk mitigation for LNG-fueled vessels. Highlights: A framework is proposed for a quantitative risk assessment of LNG-fueled vessels with respect to potential LNG leakages. ETA and CFD simulation are integrated for hazard identification, consequences analysis and LNG leakage quantification. The results of the study are used to provide risk control options in terms of optimal risk mitigation for LNG-fueled vessels.